Penerapan Pembelajaran Kooperatif Tipe Make A Match untuk Meningkatkan Hasil Belajar Mata Pelajaran IPS - Annisa Nidaur Rohmah; Silvi Robiyatul Laily (IBTIDA', 2020)
This research is motivated by a phenomenon that occurred in one elementary school in Lamongan region. School that have some students who study learning outcomes in social science learning (IPS) and have not reached the minimum completeness criteria (KKM) defined by the institution. The purpose of this research is to describe teacher activity and student activity and improve learning result of IPS through applying cooperative learning to make game to improve IPS learning result in third grade student of elementary school. Based on the results of this study, it can be concluded that the implementation of cooperative learning model type make a match can improve the activity and learning outcomes IPS students class III SD Negeri Bulu Tengger Kecamatan Sekaran Lamongan District Lessons year 2017/2018.